Associations' agreement and the interest of the network suppliers: the strategic use of structural features - Thomas Wein (Universität Lüneburg, Institut für Volkswirtschaftslehre, 2005)
The EU electricity directive (96/92/EC) established the right of the member states to choose between Regulated and Negotiated Third Party Access (RTPA and NTPA). The interest group theory is able to explain whether the introduction of NTPA in Germany had been an interest group equilibrium under the restriction of EU-directive. Using the NTPA associations of electricity power suppliers, network monopolists and industrial consumers negotiated three agreements. The last one (AA VVII+) in December 2001 introduced a market comparison scheme with three structural features: “East-/West-Germany”, “consumption/population density”, and “cable rate”. These features are variables which are supposed to reflect cost differences between network suppliers. The theoretical analysis will derive the hypothesis that this conception allows to introduce a cost irrelevant factor and therefore to increase prices without harming firms which do not hold this factor. This hypothesis could be tested by analyzing the German low and medium voltage network suppliers in 2002 and 2003. Our estimations show that the use of structural feature “East-/West Germany” and “consumption/population density” could be explained by this hypothesis. But because we have no firm specific information about cost differences other explanations could not be excluded: Monopoly prices differ with marginal costs, and regulation could reflect real cost differences. The third structural feature “cable rate” has no influence in low voltage networks, but has an impact on access charges levied in medium voltage networks. This relationship is only given if we use the borderlines given by AA VVII+. Hence, we are not able to reject the interest group theory: The feature “cable rate” was introduced successfully to increase access charges for medium network suppliers which have high cable rates without having higher costs.
Keywords: D42; L43; L94; 330; deregulation; natural monopoly; interest groups; Elektrizitätspolitik; Interessenpolitik; Energieverbund; Theorie; Deutschland